House arrest as a preventive measure - Buzescu, Gheorghe (Eximia, 2024)
Judges have applied house arrest as an alternative to imprisonment since the 17th century. Authorities have often used house arrest to detain political leaders ousted from power following a coup, but this method has been rarely used against common law offenders . The introduction of house arrest into Romanian legislation, with the entry into force of the New Criminal Procedure Code, has sparked numerous debates regarding the preventive nature of this measure and its implications on the restriction of rights such as liberty, free movement, or the presumption of innocence. Considering that in the criminal process, the means of administering justice, such as the administration of evidence, also involve the application of preventive measures aimed at ensuring the proper administration of evidence, preventing the commission of new crimes, and achieving the purpose of the criminal process, house arrest emerges as a necessary, less severe alternative to preventive detention. Currently, compared to other European criminal procedural legislations, house arrest in the Romanian legal framework is regulated and implemented in one of two ways. In Romania, house arrest is exclusively regulated as a preventive measure involving the deprivation of liberty during criminal proceedings, and not as an alternative method of serving a prison sentence. The year 2020 brought the popularization of the term "pandemic," naturally in reference to SARS-CoV-2, while simultaneously creating new legal scenarios. The "state of emergency" imposed restrictions similar to those of preventive measures involving the deprivation of liberty. The significant difference, however, was that the restrictive measures during the state of emergency applied to the entire population and aimed to protect the public from mass infection. Although both ironic and harsh, the state of emergency led to an unintended practical experiment with some of the restrictions imposed by house arrest as a preventive measure. Moreover, since the entry into force of the New Criminal Procedure Code and up to the present, the preventive measure of house arrest has included only in theory the possibility of electronic monitoring. New possibilities in this regard emerged with the adoption of Law no. 146 of May 17, 2021, concerning electronic monitoring in judicial and penal enforcement procedures. This law provides clarifications regarding electronic monitoring devices and addresses a legislative gap regarding the failure to comply with the obligation not to leave the domicile, except in expressly provided situations, now classified as the offense of escape . Finally, I aim to support the legal nature of house arrest by categorizing it, if further confirmation were needed, as a measure involving deprivation of liberty, as recognized by the jurisprudence of the European Court of Human Rights (ECHR), particularly in the cases of Manzoni v. Italy and Lavents v. Latvia .